Case Report: A case of Chlamydia psittaci infection in an HIV patient - Yao, Wenwu; Yang, Xuhui; Shi, Jinchuan; Yang, Zhangnv; Yao, Ying; Kou, Jun; Liu, Shelan; Wang, Linbo; Wu, Zhuoyin; Shi, Guoxiang; Yan, Hao; Song, Yajun (Frontiers in Cellular and Infection Microbiology, 2023)
Chlamydia psittaci is the pathogen of psittacosis and infects a wide range of birds and even humans. Human infection occurs most commonly in those with a history of contact with birds or poultry. We describe a case of psittacosis in a human immunodeficiency virus infected patient in Zhejiang Province for the first time. C. psittaci infection was confirmed by nested polymerase chain reaction (PCR) and Real-Time PCR. Phylogenetic analysis revealed that the sequences from the patient’s samples clustered with genotype A in the same branch. Our study highlights the possibility of diagnosing psittacosis in patients with a chronic disease such as HIV-infected patients, and should increase awareness and surveillance of psittacosis in China.